Electrochemical Determination of Amprolium Hydrochloride in Chicken Meats and Eggs: Food Safety Control and Theoretical Study. Issue 3 (26th March 2021) - Elsonbaty, Ahmed; Abdel-Raoof, Ahmed M.; Abdulwahab, Sara; Hassan, Wafaa S.; Eissa, Maya S.
Abstract : Food safety has come to pass as an essential part of the appropriate production operation to fulfill the definitely negative reactions of consumers and consumer organizations to current crises in the food-animal industry. The goal of this work is to establish simple and accurate potentiometric polyvinyl chloride (PVC) membrane sensors based on cyclodextrin, for rapid in situ detection and quantification of Amprolium HCl (AMP) in different matrices (pharmaceutical preparation, chicken meats, and eggs) with lower detection limits. Molecular modeling was utilized to predict the structure of the inclusion complex formed between AMP and cyclodextrin. α -cyclodextrin based sensor exhibited better performance and displayed a linear dynamic range of 1 × 10 −6 to 1 × 10 −2 M while β - and γ -cyclodextrin revealed a linear range of 1 × 10 −5 to 1 × 10 −2 M with Nernstian slopes of 29.7, 27.3, and 26.2 mV decade −1 and detection limits of 5.01 × 10 −7, 1.58 × 10 −6, and 2.51 × 10 −6 M for α -, β -, and γ -cyclodextrin based sensors respectively.